2013
DOI: 10.1111/dar.12048
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy of amphetamine‐type stimulant dependence: An update

Abstract: Issues Methamphetamine or amphetamine-type stimulants are the second most frequently used illicit drug worldwide, second only to cannabis. Behavioural treatments are efficacious, but their impact is limited underscoring the need for other treatment options, notably, pharmacotherapy. Approach A review of randomised controlled trials of pharmacotherapies for methamphetamine or amphetamine-type stimulants was performed using PubMed and Google Scholar databases. Evidence for efficacy of medications is reported. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 112 publications
0
76
0
2
Order By: Relevance
“…However, abstinence was significantly higher in those individuals with high medication adherence compared to those with low adherence in a patient population with low methamphetamine abuse (Heinzerling et al, 2014). Together, these findings suggest that a high degree of personalization and management is needed (Brensilver, Heinzerling, & Shoptaw, 2013). A trial in adolescent methamphetamine abusers/dependent individuals did support bupropion as a treatment for this subpopulation of patients .…”
Section: Bupropionmentioning
confidence: 86%
“…However, abstinence was significantly higher in those individuals with high medication adherence compared to those with low adherence in a patient population with low methamphetamine abuse (Heinzerling et al, 2014). Together, these findings suggest that a high degree of personalization and management is needed (Brensilver, Heinzerling, & Shoptaw, 2013). A trial in adolescent methamphetamine abusers/dependent individuals did support bupropion as a treatment for this subpopulation of patients .…”
Section: Bupropionmentioning
confidence: 86%
“…Studies have shown no broadly effective pharmacotherapy for treating ATS dependence [7]. Some studies show that methylphenidate, naltrexone, bupropion and mirtazapine are moderately effective for a few subgroups of patients in reducing stimulant use (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Efficacious pharmacotherapies for MA use disorder remain elusive despite extensive research on the neurobiology of the effects of amphetamines (Brensilver et al, 2013;Elkashef et al, 2008). Naltrexone (NTX) is an opioid receptor antagonist with empirically supported efficacy and FDA approval for the treatment of alcoholism (Anton et al, 2006;O'Malley et al, 1992;Volpicelli et al, 1992) and opioid dependence (Cornish et al, 1997).…”
Section: Introductionmentioning
confidence: 99%